Gharar in Sharia Financial Products: Forms, Implications, and Prevention Measures - Nurul Fatimah; Kamaruddin Kamaruddin; Supriadi Supriadi (AHKAM, 2025)
This article examines the concept of gharar (uncertainty) in Islamic financial products, focusing on its forms, impact on contract validity, and preventive measures grounded in Islamic law. Employing a qualitative-descriptive approach through a literature study method, the research draws on classical and contemporary Islamic jurisprudence, fatwas from the National Sharia Council (DSN-MUI), and practical applications within Islamic financial institutions. The findings categorize gharar into two types: gharar yasir (minor uncertainty), which is tolerated, and gharar kabīr (major uncertainty), which is prohibited due to its potential to invalidate contracts. Common manifestations of gharar in modern financial transactions include ambiguous contract terms, fluctuating pricing, uncertain delivery times, and vague descriptions of goods. These elements can compromise contractual fairness and transparency, undermining the foundational principles of Islamic finance. To mitigate gharar, Islamic financial institutions implement transparent contract structures, utilize Sharia-compliant contracts such as murābaḥah, ijārah, and muḍārabah, and operate under the oversight of Sharia Supervisory Boards (DPS). Practical implementations in Islamic banking and fintech sectors demonstrate how gharar can be effectively minimized, reinforcing both prudence and adherence to Sharia principles.